# (Why) is $p \land \lnot(p \land \lnot q) \Leftrightarrow p \land q$?

I'm trying to understand a proof for $B \cap A = A \setminus (A \setminus B)$, with $B \subseteq A$ which goes like this:

In general: $y \in A \setminus B \Leftrightarrow y \in A \land \lnot(y \in B)$

$x \in A \setminus (A \setminus B)$

$\Leftrightarrow x \in A \land \lnot(x \in A \land \lnot(x \in B))$

$\Leftrightarrow x \in A \land \lnot (x \in A) \lor \lnot\lnot(x \in B)$

$\Leftrightarrow x \in A \land \lnot (x \in A) \lor (x \in B)$

$\Leftrightarrow x \in A \land x \in B$

I don't understand how the last step works. In a footnote it says that $p \land \lnot(p \land \lnot q)$ is equivalent to $p \land q$. I don't quite understand why though. Could someone explain?

• Um, do you mean if $B\subset A$ then $B=A \setminus (A \setminus B)$? Because $B \subseteq A = A \setminus (A \setminus B)$ is not true. – Thomas Andrews Oct 29 '15 at 17:30
• Don't remove the parenthesis: $U\land (V\lor W)$ is different than $(U\land V)\lor W$. – Thomas Andrews Oct 29 '15 at 17:32
• Whoops, I mixed some things up, I corrected it. – logicislogical Oct 29 '15 at 17:34
• Well, now it's true, but the condition $B\subseteq A$ is not required for it to be true. – Thomas Andrews Oct 29 '15 at 17:35

\begin{align} p \land \lnot (p \land \lnot q) &= p \land (\lnot p \lor q) &\qquad \mbox{de Morgan rule}\\ &= (p \land \lnot p) \lor (p \land q) &\qquad \mbox{By distributivity}\\ &= (p \land q) &\qquad \mbox{since $x \land \lnot x = 0$ and $0 \lor x = x$} \end{align}